Influence of duration of preoperative treatment with phenoxybenzamine and secretory phenotypes on perioperative hemodynamics and postoperative outcomes in pheochromocytoma and paraganglioma - Yao, Yao; Guo, Ying; Fan, Jing; Lin, Tianxin; Wang, Lin; Zhang, Shaoling (Frontiers in Endocrinology, 2023)
Objectives: Resection of pheochromocytoma and paraganglioma (PPGL) carries risks with perioperative hemodynamic instability. Phenoxybenzamine (PXB) is a commonly used α-blockade to prevent it. It is unclear whether lengthening the preoperative duration of PXB is better for hemodynamic stability and postoperative outcomes. Furthermore, different types of catecholamines have varying effects on perioperative hemodynamics. Thus, our study aimed to investigate the impact of the duration of preoperative preparation with PXB and secretory phenotypes of the patients on intraoperative hemodynamic stability and postoperative complications in PPGL. Methods: Between Dec 2014 and Jan 2022, 166 patients with PPGL were operated on by the same team at Sun Yat-sen Memorial hospital. They were divided into group A(1-14d), Group B(15-21d) and Group C(>21d) based on the duration of management with PXB and into the adrenergic and the noradrenergic phenotype group based on secretory profiles. Data on intraoperative hemodynamics and postoperative outcomes were collected and compared among groups. Results: A total of 96 patients occurred intraoperative hemodynamic instability, and 24 patients had 29 postoperative complications related to the surgery. Among the 145 patients treated with PXB, no significant differences were found in the cumulative time outside the target blood pressure(6.67%[0-17.16%] vs. 5.97%[0-23.08%] vs. 1.22%[0-17.27%]，p=0.736) or in the median total HI-score(42.00[30.00-91.00] vs. 89.00[30.00-113.00] vs. 49.00[30.00-93.00]，p=0.150) among group A(n=45), B(n=51) and C(n=49). Multivariate analysis demonstrated that the level of plasma free metanephrine(MN) was an independent risk factor for intraoperative hemodynamic instability. And the median cumulative time outside of the target blood pressure in the adrenergic phenotype group was significantly greater than that in the noradrenergic phenotype group(8.17%[0-26.22%] vs. 1.86%[0-11.74%]，p=0.029). However, the median total HI-score(99.50[85.00-113.25] vs. 90.00[78.00-105.00]，p=0.570) and postoperative outcomes showed no differences between the two groups. Conclusions: A preoperative duration of nearly 14 days with PXB is sufficient for ensuring intraoperative hemodynamic stability in PPGL. And lengthening the preparation duration may not provide additional benefits in the era of widespread application and advanced techniques of laparoscopic surgery. Additionally, patients with the adrenergic phenotype are more prone to intraoperative hemodynamic instability than the noradrenergic phenotype. Thus, more attention should be given to the adrenergic phenotype during surgery.